Asynapsis and meiotic restitution in tomato male meiosis induced by heat stress - Schindfessel, Cédric; De Storme, Nico; Trinh, Hoang Khai; Geelen, Danny (Frontiers in Plant Science, 2023)
Susceptibility of the reproductive system to temperature fluctuations is a recurrent problem for crop production under a changing climate. The damage is complex as multiple processes in male and female gamete formation are affected, but in general, particularly pollen production is impaired. Here, the impact of short periods of elevated temperature on male meiosis of tomato (Solanum lycopersicon L.) is reported. Meiocytes in early-stage flower buds exposed to heat stress (>35°C) exhibit impaired homolog synapsis resulting in partial to complete omission of chiasmata formation. In the absence of chiasmata, univalents segregate randomly developing unbalanced tetrads and polyads resulting in aneuploid spores. However, most heat-stressed meiotic buds primarily contain balanced dyads, indicating a propensity to execute meiotic restitution. With most meiocytes exhibiting a complete loss of chiasma formation and concomitantly showing a mitotic-like division, heat stress triggers first division restitution resulting in clonal spores. These findings corroborate with the plasticity of male meiosis under heat and establish a natural route for the induction of sexual polyploidization in plants and the engineering of clonal seed.